Assessing the Effect of a Hospice and Palliative Medicine Curriculum on Emergency Medicine Residents' Knowledge. (May 2023) - Nguyen, David; Matese, Thomas
Background : In the average Emergency Medicine (EM) residency program there is little formal Hospice and Palliative Medicine (HPM) training, despite these skills used frequency in the Emergency Department (ED) setting, from symptomatic management to end of life communications.Objective : This research project aims to determine if a Free Open Access Medical Education based HPM curriculum will improve knowledge and comfort level of end-of-life care in EM residents within the ED. The curriculum consisted of an in-person lecture series along with self-directed learning through online modules covering a variety of foundational topics.Methods : A 10-point Likert-scale pre- and post-intervention self-survey, assessing HPM comfort level and foundation/knowledge base and skills, was administered to the residents.Results : 16/18 residents (89%) responded to the pre-intervention survey and 13/18 residents (72%) answered the post-intervention survey. There was a statistically significant increase of the residents' understanding of the difference between hospice and palliative care (pre-intervention mean of 4.44, post-intervention mean of 7.69, P = .004), as well as their perspective of how often they consult those services for patients they see in the ED (pre-intervention mean of 2.19, post-intervention mean of 3.92, P = .02) and their overall understanding of the foundations of this field (pre-intervention mean of 4.19, post-intervention mean of 7.23, P = .0002).Conclusion : The curriculum increased the EM residents' understanding of the foundations of the HPM field, their fundamental knowledge of the differences between the 2 disciplines, and the frequency of how often they consult these specialties in the ED.